Successful surgical management of a through-and-through right atrial penetrating injury with a complete transaction of the right internal mammary artery: a case report. Issue 1 (9th January 2021) - Albabtain, Ibrahim; Albargawi, Ali; Almalki, Sami A; Alnasser, Mohammed
Abstract: An injury to the pericardium or the great vessels is considered a true medical emergency, with a poor survival rate. The early identification and immediate response from all the medical services play a significant role in the management of this type of injury. In this case report, we report a young male patient brought to the emergency room (ER) after sustaining two stab wounds to the chest. We present the successful management of the patient from admission to the ER until discharge a few days later, after a successful surgical intervention for a penetrating cardiac injury.